Haptoglobin-hemoglobin receptor independent killing of African trypanosomes by human serum and trypanosome lytic factors - Bullard, Whitney (Landes Bioscience, 2012)
The haptoglobin-hemoglobin receptor (HpHbR) of African trypanosomes plays a critical role in human innate immunity against these parasites. Localized to the flagellar pocket of the veterinary pathogen Trypanosoma brucei brucei this receptor binds Trypanosome Lytic Factor-1 (TLF-1), a subclass of human high-density lipoprotein (HDL) facilitating endocytosis, lysosomal trafficking and subsequent killing. Recently, we found that group 1 Trypanosoma brucei gambiense does not express a functional HpHbR. We now show that loss of the TbbHpHbR reduces the susceptibility of T. b. brucei to human serum and TLF-1 by 100- and 10,000-fold, respectively. The relatively high concentrations of human serum and TLF-1 needed to kill trypanosomes lacking the HpHbR indicates that high affinity TbbHpHbR binding enhances the cytotoxicity; however, in the absence of TbbHpHbR, other receptors or fluid phase endocytosis are sufficient to provide some level of susceptibility. Human serum contains a second innate immune factor, TLF-2, that has been suggested to kill trypanosomes independently of the TbbHpHbR. We found that T. b. brucei killing by TLF-2 was reduced in TbbHpHbR-deficient cells but to a lesser extent than TLF-1. This suggests that both TLF-1 and TLF-2 can be taken up via the TbbHpHbR but that alternative pathways exist for the uptake of these toxins. Together the findings reported here extend our previously published studies and suggest that group 1 T. b. gambiense has evolved multiple mechanisms to avoid killing by trypanolytic human serum factors.